Buddhist Principles According to Psychology for Sustainable Development - Srilasudtro, Phrabaidika kittipong; Srivichitvorakul, Sompoch (Mahachula Academic Journal, 2021)
The principles of Buddhism in accordance with the psychology for sustainable development must be practiced by the Threefold Principles. to further train the body, speech, mind and wisdom until reaching the ultimate goal, which is Nirvana according to the concept of Buddhism Self development is learning and practice. in order to fit balance of life There is a harmonious relationship between the person’s lifestyle and the environment. and focus on making yourself happy self-aware Self-understanding rather than material dependence Therefore, it is a guideline for sustainable life development. By developing oneself according to the Buddhist Dharma in 3 ways: (1) Tama means knowing and restraining one’s mind. self improvement training by doing good deeds (2) Sikkha is education for enlightenment. know the benefits See everything as a learning to improve and develop yourself (3) Bhavana is the practice of vipassana meditation according to the four foundations of mindfulness, which is the use of mindfulness and wisdom to determine the realization of form-name, physical condition, feeling, mind and dharma according to reality. and behaviorism psychology that is the principle of behavior change in self development or improvement born of learning is the result of human interaction with the environment. And the behavior of the person expressed can be changed. Due to the karma that occurs in that environment, there are two types of karma: (1) Karma that is a positive reinforcement (2) Negative reinforcement can help a person to remove unsatisfactory environmental stimuli.